Handbook of the Freshwater Fishes of India - R Beavan; BEAVAN (R) (Chennai Maven Books, 2020)
Originally published in 1877,this little book was intended by the author to be used as a handbook or for reference. It is not an extensive research into the various fishes of India, but can be used by anyone with an interest in the subject. Contents include: On Ichthyology in General, and that of the Indian Fresh Waters in Particular - On Classification - On Distribution - Descriptions of some of the Principal Families of Fish - Of The Species and Genera Inhabiting the Fresh Waters of the Indian Continent - Habits, Breeding Etc. - List of Freshwater Fishes of the Indian Continent - Index to Native names and Synonyms - List of References and Abbreviations.